The definitive ANTLR reference : building domain-specific languages. - Parr, Terence, ....- (Raleigh : The pragmatic bookshelf, 2007)
ANTLR is a parser generator: a program that generates code to translate a specified input language into a nice, tidy data structure. You might think that parser generators are only used to build compilers. But in fact, programmers usually use parser generators to build translators and interpreters for domain-specific languages such as proprietary data formats, common network protocols, text processing languages, and domain-specific programming languages. Domain-specific languages are important to software development because they represent a more natural, high fidelity, robust, and maintainable means of encoding a problem than simply writing software in a general-purpose language. For example, NASA uses domain-specific command languages for space missions to improve reliability, reduce risk, reduce cost, and increase the speed of development. Even the first Apollo guidance control computer from the 1960s used a domain-specific language that supported vector computations. This book is the definitive guide to using the completely rebuilt ANTLR v3 and describes all features in detail, including the amazing new LL(*) parsing technology, tree construction facilities, StringTemplate code generation template engine, and sophisticated ANTLRWorks GUI development environment. You'll learn all about ANTLR grammar syntax, resolving grammar ambiguities, parser fault tolerance and error reporting, embedding actions to interpret or translate languages, building intermediate-form trees, extracting information from trees, generating source code, and how to use the ANTLR Java API.
Keywords: Programmeren; ANTLR